Keep it going: maintaining health conversations using relational and instrumental approaches. Issue 3 (3rd March 2016) - Traino, Heather M.; Siminoff, Laura A.
ABSTRACT: The initial moments of conversations, particularly discussions addressing difficult or unexpected health topics, establish the context and tone of the entire discussion. We examined how elements of relational and instrumental communication occurring within the first five minutes of the request impacted the length of the discussion. A sample of 16 U.S. tissue banking organizations and their staff (n = 226) making telephone requests for donation to families of tissue-donation eligible patients (n = 1, 465) agreed to participate in the research. The first five minutes of 430 (29.4%) audiorecorded request conversations were qualitatively coded and analyzed. The primary outcome measure was whether the conversation continued beyond the first five minutes (yes/no). Aspects of both relational and instrumental communication were associated with discussion length. A logistic regression analysis found that the total number of distinct topics disclosed and requesters' vocal affect during the discussion as well as characteristics of the family member approached about donation predicted conversational maintenance. This research demonstrates that "thin slices" of effective relational and instrumental communication can have a significant, positive impact on conversation length.